Medulloblastoma with epithelioid features in the cerebellar vermis. Issue 9 (24th July 2016) - Miyata, Kenji; Hori, Toshinori; Yamakawa, Kiyoshi; Takasu, Michihiko; Hayakawa, Tomohito; Shimomura, Yasuto; Iwata, Atsuko; Okumura, Akihisa; Nakura, Takahiro; Jyoko, Masahiro; Mori, Yoshimasa; Takahashi, Emiko; et al.
Abstract: A 6‐year‐old girl was admitted with a mass lesion in the cerebellar vermis. She underwent subtotal tumor resection, and on immunohistopathology the tumor consisted of two different parts: typical medulloblastoma (MB) characteristics and atypical teratoid/rhabdoid tumor (AT/RT) features, despite positive integrase interactor 1 expression. The patient was diagnosed with MB with epithelioid features. Chemoradiation therapy was started because of tumor recurrence at the primary site and dissemination to the spinal cord, as determined on magnetic resonance imaging 2 weeks after surgery. The patient died due to tumor progression 13 months after initial diagnosis, although transient partial remission was achieved.